Pendidikan Agama Islam dan Budaya Akademik Mahasiswa: Studi Mediasi Moderasi Beragama - Af Ahmad Ramadhan (GHIROH, 2026)
This study aims to analyze the influence of Islamic Religious Education on students' academic culture with religious moderation as a mediating variable at Institute of Technology and Business Indragiri. The research approach used is quantitative with a survey method, involving students as respondents. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that Islamic Religious Education has a positive and significant effect on students' academic culture. In addition, Islamic Religious Education also has a positive and significant effect on religious moderation. Furthermore, religious moderation is proven to have a positive effect on academic culture and significantly mediates the relationship between Islamic Religious Education and students' academic culture. These findings confirm that strengthening Islamic Religious Education based on religious moderation has a strategic role in building students' academic culture in higher education.